Environmental influence of problematic social relationships on adolescents' daily cortisol secretion: a monozygotic twin-difference study. Issue 3 (21st October 2016) - Brendgen, M.; Ouellet-Morin, I.; Lupien, S. J.; Vitaro, F.; Dionne, G.; Boivin, M.
Abstract : Background: This study investigated the potential environmental effects of peer victimization and the quality of relationships with parents and friends on diurnal cortisol secretion in mid-adolescence. Method: This study used the monozygotic (MZ) twin-difference design to control for genetic effects and thus estimate the unique environmental influences on diurnal cortisol. Participants were 136 MZ twin pairs (74 female pairs) for whom cortisol was assessed four times per day over four collection days grouped in a 2-week period in grade 8 (mean age = 14.07 years). Participants also provided self-reports of peer victimization from grade 4 to grade 8 and of the relationship quality with the mother, father and best friend in grade 8. Results: The expected pattern of diurnal cortisol secretion was observed, with high levels at awakening followed by an increase 30 min later and a progressive decrease subsequently. Controlling for a host of confounders, only within-twin pair differences in peer victimization and a problematic relationship with the mother were significantly linked to twin differences in diurnal cortisol secretion. Specifically, whereas a more problematic mother–child relationship was associated with morning cortisol secretion, peer victimization was linked to cortisol secretion later in the day (diurnal slope). Conclusions: Controlling for genetic influences and other confounders, stressful relationships with peers and the mother exert unique and time-specific environmental influences on the pattern of diurnal cortisol secretion in mid-adolescence.